2007
DOI: 10.1055/s-2008-1017467
|View full text |Cite
|
Sign up to set email alerts
|

Arbeitsbedingungen und Depression bei Ärzten

Abstract: Eine erhöhte Prävalenz von Depressionen bei Ärzten, insbesondere zu Beginn der Facharztweiterbildung, trägt möglicherweise zu einem deutlich erhöhten Risiko für Ärzte, und mehr noch für Ärztinnen bei, durch einen Suizid zu sterben [3,8,25,37]. Depressionen verursachen neben individuellemLeiden ökonomische Ausfälle, durch Krankheitstage und Produktivitätsverluste ("Präsentismus"), d.h. Anwesenheit bei geringerer Leistungsfähigkeit [24]. Burnout, ein Phänomen, das zwar als berufsbezogen definiert ist, sich jedoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 34 publications
1
15
0
8
Order By: Relevance
“…Variables that have been shown to be relevant in other studies in the medical context, e.g. “unfavorable organizational work conditions in the hospital” or “overwork through lack of sleep” [15] are surely less pronounced in our target population. Although about one third of the employees of medical psychology are also active in patient care, this activity is not normally their main focus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variables that have been shown to be relevant in other studies in the medical context, e.g. “unfavorable organizational work conditions in the hospital” or “overwork through lack of sleep” [15] are surely less pronounced in our target population. Although about one third of the employees of medical psychology are also active in patient care, this activity is not normally their main focus.…”
Section: Discussionmentioning
confidence: 99%
“…Causal interpretations or statements about development are not possible. A longitudinal study design with repeated measures, which could measure changes over time and the influence of gratification crises on mental and physical health, would be desirable [15]. Capturing additional variables such as depressiveness or perceived social support at the workplace would be desirable.…”
Section: Limitationsmentioning
confidence: 99%
“…Analyses by health care insurances show that health care professionals tend to have the highest rates of health-related incapacity for work [12]. Multiple studies have shown that stress-related working conditions, such as time pressure, workload, interruptions of workflow, difficulties with patients or conflicts with co-workers and supervisors, are common in hospital workplaces [13–15] and may lead to reduced psychological and physical well-being [16, 17]. In addition, it is worth recalling that these working conditions can have negative consequences for patient outcome [16, 18].…”
Section: Introductionmentioning
confidence: 99%
“…In der wissenschaftlichen Literatur wird seit langem über die steigende Arbeitsbelastung in den Gesundheitsberufen und die daraus resultierenden gesundheitlichen Folgen berichtet [1,5,7,11,12]. Arbeitssituationen mit intensiver zeitlicher und emotionaler Belastung werden dabei immer wieder in Zusammenhang mit dem Burn-out-Phäno-men gebracht [3,6,9,13,18].…”
unclassified